The missing public domain in public spaces: A gendered historical perspective on a Latin American case - Karen HINOJOSA; Carlos ESTUARDO APARICIO MORENO (Urbani Izziv, 2016)

(untitled)
This article searches for public domains in the history of public spaces in Monterrey from the perspective of their colloquial use by different social groups. Through documentary analysis, it reconstructs the transition from publicly owned public spaces to their privatised counterparts. The article expands the traditional somewhat idyllic narrative of public spaces and offers clues to how different social groups have used them. Public spaces have changed during four main periods. A centralised public space appeared during the colonial period (1596–1810), followed by socially segregated spaces between the beginning of the war for independence until after the revolution (1810–1940). The dispersion of public space characterises the period of the metropolitan expansion of Monterrey (1940–1980). Finally, the privatisation of public spaces occurred at the turn of the millennium (1980–2015). Women, children and lower socioeconomic classes have had unequal access to public spaces in Latin America, thus precluding them from being considered public domains.